Knowledge, Risk Perception, and Reproductive Decision Making among Women with Epilepsy - Srikanth, Pallerla; Vranda, Mysore Narasimha; Thomas, Priya Treesa; Raghvendra, Kenchaiah (International Journal of Epilepsy, 2022)
Introduction Epilepsy is a neurological disorder that causes neurobiological, cognitive, and psychosocial consequences. Such impairments lead to substantial social influence on women across their life cycle stages, mostly connected with stigma, the severity of illness, quality of life, and other psychosocial issues in adding to reproductive decision-making associated to risk perception. This study aimed to assess the knowledge, risk perception, and reproductive decision-making factors among women with epilepsy.Materials and Methods A cross-sectional descriptive study was carried out to assess the knowledge, risk perception, and reproductive decision-making factors among women with epilepsy. A semistructured questionnaire was prepared to collect the sociodemographic and clinical characteristics of 49 women who sought treatment for epilepsy from a national tertiary referral care center for neuropsychiatry in South India. The researcher developed a 24-item questionnaire, including three open-ended questions to assess the knowledge about reproductive health issues and epilepsy.Results The participants' mean age was 24.67 ± 3.72, where 51% had secondary education, 63.3% were married, and 46.9% were homemakers. Women with epilepsy have reported lower knowledge about the illness and about the pregnancy, childbearing practices, breastfeeding, and epilepsy-related factors. Content analysis of responses to open-ended questions brought out the presence of marriage-related concerns, epilepsy and pregnancy, misconceptions about the pregnancy outcomes, and general misconceptions about the illness factors that play a role in reproductive decision-making among women living with epilepsy.Conclusion The study reveals that women with poor knowledge about epilepsy and pregnancy have difficulty in reproductive decision-making, thereby increasing risk perception of childbearing. This places interest on the necessity for health care professionals to address the above psychosocial problems as part of their intervention plan.
Keywords: knowledge; reproductive decision making; risk perception; women with epilepsy